2019
DOI: 10.1002/aoc.4968
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the formation of silver nano‐binuclear complex on the refinement of cytotoxic and antibacterial potency of coumarin Schiff base: Spectroscopy, thermal, X‐ray diffraction analyses and density functional theory calculations

Abstract: A new Schiff base (SCH) was prepared using 8‐acetyl‐7‐hydroxy‐4‐methylcoumarin and sulfaclozine. Its silver complex was also synthesized. These compounds were subjected to elemental and spectral analyses. The silver complex was also subjected to thermogravimetric analysis, molar conductance measurements, scanning electron microscopy, energy‐dispersive X‐ray analysis and X‐ray diffraction measurements. The formula of the complex was determined as [(Ag2SCH(NO3)2]. The molar conductance indicates its non‐electrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…[ 7 ] Silver(I) complexes of pyrazolyl s‐triazine were observed to have antimicrobial properties which depended on the nuclearity of the complexes. [ 8 ] An investigation by El‐Ansary et al [ 9 ] showed the enhanced antimicrobial activity of Ag‐coumarin complexes compared with the free ligands, and similar results were also obtained for Ag‐isonicotinic acid complexes. [ 10 ] Interestingly, Ag‐naphthalenol Schiff base complexes showed manifold pharmaceutical therapy, namely, anticancer, antioxidant and antimicrobial offering combination drug treatment at one goal.…”
Section: Introductionmentioning
confidence: 78%
“…[ 7 ] Silver(I) complexes of pyrazolyl s‐triazine were observed to have antimicrobial properties which depended on the nuclearity of the complexes. [ 8 ] An investigation by El‐Ansary et al [ 9 ] showed the enhanced antimicrobial activity of Ag‐coumarin complexes compared with the free ligands, and similar results were also obtained for Ag‐isonicotinic acid complexes. [ 10 ] Interestingly, Ag‐naphthalenol Schiff base complexes showed manifold pharmaceutical therapy, namely, anticancer, antioxidant and antimicrobial offering combination drug treatment at one goal.…”
Section: Introductionmentioning
confidence: 78%
“…In a molar ratio of (2:1) (M:L), a proper weight of copper acetate or palladium chloride dissolved in ethanol was mixed with a proper weight of Schiff base, which was prepared and characterized previously. [ 12 ] After adding a few drops of NH 4 OH, about 15 min were given for the complex to condense before being transferred to the reflux system for around 10 h. The complex was then filtered, rinsed with distilled water and hot ethanol, dried, and placed in a desiccator with dry CaCl 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Several commonly used metal ions, such as copper, zinc, and palladium, are more effective against a variety of diseases. [11] According to El-Ansary et al, [12] the nanosilver complex with coumarin Schiff base (Sb) was studied. In continuation to this work, nanocopper and palladium metal complexes of Schiff base (Sb) in addition to mixed zinc complex of Schiff base (Sb) and ciprofloxacin were synthesized and characterized using a variety of analytical methods in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The IC 50 of SCH (104) for the MCF-7 cell line was 90.5 µg/mL, while that of SCH-Ag (105) was 9.3 µg/mL. SCH (104) and SCH-Ag (105) showed less antitumor activity than cisplatin (IC 50 = 1.7 µg/mL) [114].…”
Section: Coumarin-pyrazine Hybridizationmentioning
confidence: 95%